Financial accounting theory and analysis : text and cases - Schroeder, Richard G.; Cathey, Jack M.; Clark, Myrtle W. (Wiley, 2011)
"Updated and revised, this tenth edition helps accountants build strong critical thinking skills and a sound theoretical background. This enables them to evaluate accounting practice in today?s increasingly global world economy. A unique and timely collection of cases and readings cover all areas of accounting and shows how the latest accounting standards impact decision making. New FASB codification cases provide up-to-date information. Room for Debate cases in each chapter, as well as updated disclosure examples throughout the book, also engage accountants as they learn how the material relates to their profession"